How does “home health services” training during family medicine residency influence medical practice of the physicians - CÖBEK ÜNALAN, GÜLRU PEMRA; APAYDIN KAYA, MEMNUNE ÇİĞDEM (My University, 2022)
Background: Family physician who has a key role in the provision of Home Care is considered to take part in this service delivery according to the basic discipline characteristics he/she is expected to provide this service. However, training on this topic doesn't have a standart during residency and there is no data yet on how physicians trained in HHSs and whether the training is effective in practice. Research questions: What kind of training is received during residency, perceptions of the family physicians and how it contributed to their daily practice? Method: Qualitative research method with audio recordings through focus group interviews and face-to-face structured in-depth interviews between 04,September 2021 and 04,February 2022 was used. Snowball method was used to recruit the family physicians who had HHS training during their residency. A total of 64 family medicine specialists were reached; 25 did not meet the inclusion criteria and 22 did not accept to participate in the study, a total of 16 were interviewed. Results: Physicians talked about their achievements, positive and negative experiences during residency training and providing HHSin their practice. Physicians' main argument was the HHS training is an opportunity to learn the basic principles and approaches of Family Medicine discipline. It is irreplaceably important in professional development, professional satisfaction and motivation. So the training methods and curriculum arrangements of Home Care training must be reviewed and best conditions must be integrated. They also mentioned negative experiences, too; the technical, structural and organizational problems during the consultation and referral, security concerns and physical difficulties experienced with the proxies were the emerging categories. Conclusions: HHS practicing physicians mention that HHS, Social Services and Family Medicine/Primary Care are a whole and a unique area to practice comprehensive and biopsychosocial care. So not only the effective training during residency but also the collaboration during practice is essential.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Home Health Services; home care; education; experience; family medicine; practice